Colourful Protection: Challenges and Perspectives of Antibacterial Pigments Extracted from Bacteria for Textile Applications - Micaela Gomes; Helena P. Felgueiras; Barbara R. Leite; Graça M. B. Soares (Antibiotics)
Bacterial pigments have gained significant attention across multiple industries due to their natural hues and unique functional properties. Beyond coloration, some of these pigments exhibit antibacterial activity, making them particularly valuable in the textile industry as sustainable alternatives to synthetic antimicrobial treatments. Bacteria produce a vast array of pigments through diverse biosynthetic pathways, which reflect their metabolic adaptability and ecological roles. These pathways are influenced by environmental factors such as pH, temperature, and nutrient availability. Key pigments, including carotenoids, melanin, violacein, and prodigiosin, are synthesised through distinct mechanisms, often involving tightly regulated enzymatic reactions. For example, carotenoid biosynthesis relies on isoprenoid precursors, while melanin formation involves the oxidation of aromatic amino acids. Understanding these pathways provides insights into bacterial survival strategies, stress responses, and interactions with their environment. This review examines the dyeing potential of bacterial pigments on natural and synthetic fabrics, highlighting advancements in environmentally friendly extraction methods to minimise the ecological impact. Additionally, it explores safety, biocompatibility, and industrial challenges associated with bacterial pigment applications. Finally, future perspectives on integrating these pigments into various industries are discussed, emphasising their potential as bio-based solutions for sustainable and functional materials.